Transcranial Magnetic Stimulation-Induced Motor Cortex Activity Influences Visual Awareness Judgments - Hobot, Justyna; Koculak, Marcin; Paulewicz, Borysław; Sandberg, Kristian; Wierzchoń, Michał (Frontiers in Neuroscience, 2020)
The influence of non-visual information on visual awareness judgments has recently gained substantial interest. Using single-pulse Transcranial Magnetic Stimulation (TMS), we investigate the potential contribution of evidence from the motor system to judgment of visual awareness. We hypothesized that TMS-induced activity in the primary motor cortex (M1) would increase reported visual awareness as compared to the control condition. Additionally, we investigated whether TMS-induced motor-evoked potential could measure accumulated evidence for stimulus perception. Following stimulus presentation and TMS, participants first rated their visual awareness verbally using the Perceptual Awareness Scale, after which they responded manually to a Gabor orientation identification task. Delivering TMS to M1 resulted in higher average awareness ratings as compared to the control condition, in both correct and incorrect identification task response trials, when the hand with which participants responded was contralateral to the stimulated hemisphere (TMS-response-congruent trials). This effect was accompanied by longer Perceptual Awareness Scale response times, irrespective of the congruence between TMS and identification response. Moreover, longer identification response times were observed in TMS-response-congruent trials in the M1 condition as compared to the control condition. Additionally, the amplitudes of motor-evoked potentials were related to the awareness ratings when response congruence was taken into account. We argue that motor-evoked potential can serve as an indirect measure of evidence accumulated for stimulus perception and that longer Perceptual Awareness Scale response times and higher amplitudes of motor-evoked potentials in the M1 condition reflect integration of additional evidence with visual awareness judgment. In conclusion, we advocate that motor activity influences perceptual awareness judgments.